Dynamic Interrelationships Between EAEU Foreign Trade and Macroeconomic Indicators: An Empirical Analysis - Galoyan, Diana; Matevosyan, Diana («Տնտեսագետ» հրատ․)
International trade contributes to the development of Eurasian Economic Union (EAEU) as a regional integration alliance and, as stated by classical economists, plays a decisive role in the economic growth of any country (region). Most studies of EAEU international trade flow analysis focus on the trade component. The present paper attempts to display the connection between EAEU trade and macroeconomic indicators. The applied technical methods of statistical analysis have enabled the researchers to evaluate SARIMA models for export and import, and forecast EAEU 2020 trade dynamics based on these models. Then keeping in mind, the idea that the basis of the constructed model is the assumption that the series will maintain its trend, the actual value was simply subtracted from the forecast value to measure the 2020 shock effect. Due to the fundamental methods of statistical analysis the EAEU member countries’ trade and macroeconomic indicators elasticity ratios have been calculated, which are likely to measure the impact rate and become new empirical knowledge in assessing the interaction of trade turnover and the economic growth of the countries.
Keywords: International economics